The Impact of Cybercrime on Customer Trust in Bank Syariah Indonesia - Sriwahyuni Rustan; Ifayani Haanurat; Nurlina Nurlina (Jurnal Ekonomi & Bisnis, 2026)
This study aims to analyze the influence of cybercrime on customer trust in Bank Syariah Indonesia (BSI). A quantitative approach was employed, using a survey method by distributing questionnaires to BSI customers who have used digital banking services. The research instrument was structured using a Likert scale and analyzed with the help of SPSS version 30.0. The results of the analysis indicate that cybercrime has a positive and significant effect on customer trust. This means that the higher the level of threat or experience related to cybercrime, the greater the impact on decreasing customer trust in the security and digital services provided by the bank. These findings also reveal that customers' perceptions of digital security greatly influence their confidence in conducting banking transactions. Therefore, banking institutions, particularly BSI, need to strengthen their cybersecurity systems, continuously educate customers about digital safety, and ensure transparency in handling security incidents to maintain and enhance customer trust. This research contributes to the existing literature on customer trust and highlights the importance of data protection in the era of banking digitalization.